READING STRATEGIES APPLIED BY BENGKAYANG STUDENTS TO OVERCOME THEIR COMPREHENSION PROBLEMS - Nelly, Ventaria; Setiamunadi, Antonina Anggraini (IJIET (International Journal of Indonesian Education and Teaching), 2024)
Reading is one of the language skills that learners must acquire. However, many students experience difficulties because they lack English knowledge. There are strategies that students can use to overcome their reading difficulties such as translating, asking questions, and using other references. Research about English reading strategies has been conducted in several regions in Indonesia such as in Aceh Besar and Medan, but in Bengkayang, there has never been any research done on that topic. Thus, this study aimed to find out Bengkayang senior high school students’ strategies to overcome their English reading difficulties. The participants of this study were 90 first-grade senior high school students from four senior high schools in Bengkayang. This study uses a quantitative descriptive method by using a questionnaire as its data collecting instrument. The questionnaire contains three open-ended questions and sixteen closed-ended questions. The findings showed that Bengkayang students faced some problems in reading English texts such as lack of vocabulary and grammatical mastery. The strategies to overcome the difficulties are divided into three categories Support, Problem-solving, and Global strategies. Based on the findings, Problem-Solving strategies are the type of strategies that the students often use while comprehending reading texts.